Taxonomy and conservation of the Brazilian extra-Amazonian species of Philodendron subg. Pteromischum (Araceae) - Barbosa, Juliana Ferreira; Sakuragui, Cassia Monica (Phytotaxa, 2014)
Philodendron subg. Pteromischum is one of the three Philodendron subgenera and most diverse within Amazonia. It can be recognised by anisophyllous sympodial growth, long sheaths, short petiole, gynoecia with broad shallow compitum, and numerous ovules per locule. The taxonomic revision for Brazilian extra-Amazonian species was based on the analysis of 590 herbaria specimens. Nine Brazilian extra-Amazonian Pteromischum species were recognized, five names previously recognised for the studied area were treated as synonyms. All the species were described and mapped. An identification key and comments on taxonomy, nomenclature, conservation, phenology were provided for each species. The concepts of leaf-sheath and petiole are also clarified.